False-positive 1p/19q Testing Results in Gliomas: Clinical and Research Consequences. (November 2020) - Alnahhas, Iyad; Rayi, Appaji; Thomas, Diana; Ong, Shirley; Giglio, Pierre; Puduvalli, Vinay
Abstract : Background: The revised fourth edition of the World Health Organization Classification of Tumors of the Central Nervous System—published in 2016—established 1p19q codeletion as the molecular hallmark for the diagnosis of oligodendrogliomas. Fluorescence in situ hybridization (FISH) is currently the most commonly used modality for 1p19q testing. However, as with most laboratory testing, 1p19q FISH testing has a false-positive rate, potentially resulting in an erroneous diagnosis of oligodendroglioma with significant implications for the choice of therapy and prognosis. Methods: The authors describe a case series of 5 patients treated at the Ohio State University James Cancer Center to illustrate the problem of false-positive 1p19q FISH results. Results: In our case series, the authors present a spectrum of possibilities for conflicting 1p19q testing results and the clinical consequences. The authors present 4 cases that, in retrospect, are believed to have had a false 1p19q FISH results. One other case may represent a true transformation of oligodendroglioma to glioblastoma or a second malignancy. Neuro-oncologists should pay attention to additional molecular markers, namely ATRX, TP53, and MGMT methylation status, before discussing the pathology with the patient and formulating a treatment plan. Conclusions: Pathologists and neuro-oncologists should be aware of false-positive 1p19q FISH results as they can significantly change treatment and prognosis for glioma patients. Moreover, this issue should be taken into account when designing clinical trials specific to this disease cohort.